Perubahan Semantik Kosakata Serapan Bahasa Asing dalam Bahasa Indonesia - Nadya Fitri Lestari; Mohd. Harun; Siti Sarah (Universitas Negeri Makassar, 2021)
Abstract. This study aims to describe the changes in meaning that occur in foreign language absorption vocabulary in Indonesian. The data source in this study is Indonesian vocabulary absorbed from Foreign languages, namely Dutch and English. The data in this study is a dictionary of foreign absorption words in Indonesian by J.S Badudu. Data collection techniques using document review techniques. This research uses qualitative approach and research type using descriptive method. The results of this study researchers found the words absorption that experienced a change in meaning, as for the word absorption that experienced changes in meaning in the form of expansion, narrowing and total changes. The expansion of meaning is a process that occurs in a word that at first only has a meaning, but then because various factors become have other meanings. The Dutch example of the word